Dicey's song - Voigt, Cynthia (New York : Atheneum Books for Young Readers, 2012)
Now that the four abandoned Tillerman children are settled in with their grandmother, Dicey finds that their new beginnings require love, trust, humor, and courage.
Sequel to: Homecoming.
Keywords: Brothers and sisters -- Fiction; Family life -- Fiction